In vitro Propagation of Thuja occidentalis Through Apical Shoot Culture (Plant Tissue Culture and Biotechnology, 2008)
In vitro plant regeneration of Thuja occidentalis was obtained in apical shoot cultures from field grown plants. Hormone free MS medium 100% explants produced shoots. The average number of shoots per explant was 6.57 ± 0.45 and the average shoot length of 4.5 ± 0.27 cm were recorded in this medium. Shoots rooted well when they were transferred into half strength MS with 1.0 mg/l IBA. The average number of root per shoot was 3.92 ± 0.28 and the average root length of 3.64 ± 0.38 cm were observed in this medium. No morphological variants were observed during the passage of in vitro culture.Key words: In vitro, Propagation, Thuja occidentalis, Apical shootDOI = 10.3329/ptcb.v16i1.1099Plant Tissue Cult. & Biotech. 16(1): 5-9, 2006 (June)